Analysis of drawing characteristics for reproducing traditional hand-made stippling. (May 2019) - Martín, Domingo; Arroyo, Germán; del Sol, Vicente; Romo, Celia; Isenberg, Tobias
Highlights: A study about the appearance of hand-placed dots in traditional stippling. A discussion of stipple dot reproduction on typical output devices. A discussion the effects of dot attributes on the perception of digital stippling. Graphical abstract: Abstract: We contribute an in-depth analysis of the characteristics of traditional stippling and relate these to common practices in non-photorealistic stippling as well as to the abilities and limitations of existing printing and display technologies. Based on the properties of traditional stipple dots which depend on the used pens and paper types, we focus on a perceptual study of digital stippling that further informs our discussion and work toward an understanding of the requirements for the reproduction of hand-made stippling. To allow artists and illustrators to replicate the stippling process faithfully in the digital domain, we thus extract guidelines from the study results such as that the characteristics of real dots must be reproduced because they are perceived and that the results must be adjusted to the different properties of output devices.